Perlindungan Hukum Konsumen Bagi Korban Atas Peredaran Minuman Keras Oplosan - Grace Angelia Soenartho; Tundjung Herning Sitabuana (Jurnal Indonesia Sosial Teknologi, 2022)
There are adulterated liquors that can often be found in the community, but do not have a distribution permit and these mixed liquors contain harmful substances such as methanol, acetone and ethanol which can cause harm to consumers from minor to death. However, the government's policy of opening up investment flows for the alcohol-based liquor industry prioritizes the interests of entrepreneurs rather than the interests of the people. Furthermore, it is necessary to standardize the quality of alcoholic beverages circulating in the general public, so that it can be ensured that alcoholic beverages in circulation are those that meet the standards for consumption. This study aims to protect consumers from consuming alcoholic or counterfeit alcoholic beverages and to find out the regulation of the Papua Province regional regulations for consumers and business actors to be responsible for consumer losses related to their production goods that are not in accordance with their composition. The results of this study indicate that business actors must be responsible for their actions that are detrimental to consumers, which can damage the health of consumers who consume these fake products in the long term, it can damage their organs. Then, regarding the legal sanctions contained in the regional regulations of the Papua Province, Anyone who violates the provisions of Article 5, Article 6, Article 7, is threatened with imprisonment of 5 (five) years or a fine of Rp. 1 billion. with a maximum imprisonment of 6 (six) months and/or a maximum fine of Rp. 50 million.